Impact of merger on efficiency and productivity: a case study of commercial banks in Malaysia / Mahadzir Ismail ...[et al] - Ismail, Mahadzir; Sulaiman, Saliza; Abdul Rahim, Hasni; Nordin, Nordiana (Research Management Institute, 2008)
The Financial Master Plan (2001-2010) aims to enhance the capacity of banking industry so that higher efficiency and productivity can be reaped in the future. This study seeks to determine the impact of merger on efficiency and productivity of commercial banks in Malaysia for the period 1995 until 2005. The study uses a non-parametric approach, namely DEA to estimate the efficiency scores and to construct the Malmquist productivity index. To enable this estimation, three bank inputs and outputs are used. Amongst the findings are those banks exhibit higher efficiency score after the merger and the foreign banks are more efficient than the local bank. For productivity, the banks have improved in both periods, before and after the merger. However, it is the local banks that have improved the most after the merger. The main source of productivity is technical change or innovation. The findings support the existing policy of having larger domestic banks in term of size/Mahadzir Ismail...[et.al.]